Peran guru dan orang tua dalam pendidikan karakter sejak masa sekolah di era digital - Hanifah, Hanhan (Maliki Interdisciplinary Journal, 2024)
MTs Almaarif 01 Singosari creates a learning environment that is good, polite, Islamic, and has the character of ahlusunnah wal jamaah an nahdliyah. Building a young generation with character in the digital era requires comprehensive collaboration from parents, educators and the school environment. Instilling positive values, such as mutual respect, respect and empathy, is the main key. Parents act as role models, schools design appropriate curricula, and a positive and supportive school environment provides a platform for students to develop. This collaboration is important to create a young generation with integrity and resilience in facing various challenges in the digital era. Character education can be concluded as an education containing values, character, morals and character, which aims to develop students’ abilities to make good and bad decisions, maintain what is good, and realize that goodness in everyday life wholeheartedly.